IMPLEMENTATION OF SES TECHNIQUES IN THE NEEDS FOR BROILER CHICKEN MEAT IN ASAHAN DISTRICT - Maulana Marpaung, Teguh Gilang; Ramdhan, William; Syahputra, Abdul Karim (JURTEKSI (jurnal Teknologi dan Sistem Informasi), 2024)
Abstract: The Asahan Regency Animal Husbandry and Animal Health Service carries out outreach activities on the level of demand for boiler chicken, which means that the department must be more active in collecting data on the volume of boiler chicken every year because consumer demand for chicken continues to increase and instability often occurs. Where in the period 2012 to 2024 there was a significant increase in demand. So it becomes an obstacle in the stock of chickens in the Asahan Regency market which must be prepared. If there is too much chicken supply but the demand for chicken consumption decreases then this will result in a loss, conversely if the demand for chicken consumption increases but the chicken supply cannot be prepared then this will be a loss for chicken traders and distributors. To increase the accuracy of the estimates, the use of the Single Exponential Smoothing Method is proposed. This method smooths past values with exponential weights, placing greater emphasis on recent data. Using data from the last 12 (twelve) years as reference data for recording the past for forecasting experiments for the next 1 (one) month. Experiments using different Alphas test accuracy in actual situations. The results of the experiment with an alpha of 0.9 are almost the same as the actual value in predicting the situation one year into the future with the lowest error, namely MAPE 7.4% and forecasting broiler chicken meat supplies of 13661261.46 chickens.Keywords: broiler chicken; ses method; web based. Abstrak: Dinas Peternakan dan Kesehatan Hewan Kabupaten Asahan melakukan aktivitas penyuluhan tingkat  permintaan ayam boiler dimana pihak dinas harus lebih aktif dalam melakukan pendataan volume ayam boiler setiap tahunnya karena permintaan konsumen terhadap ayam sering terjadi ketidakstabilan. Dimana pada periode tahun 2012 sampai dengan 2024 terjadi kenaikan permintaan yangsignifikan. Sehingga menjadi kendala dalam stok ayam di pasar Kabupaten Asahan yang harus disiapkan. Jika persediaan ayam terlalu banyak namun permintaan akan konsumsi ayam menurun maka ini akan manjadi kerugian, sebaliknya jika permintaan akan konsumsi ayam meningkat namun persediaan ayam tidak dapat disiapkan maka ini menjadi kerugian bagi pihak pedagang dan distributor ayam. Untuk meningkatkan ketepatan perkiraan, penggunaan Metode Single Exponential Smoothing diusulkan. Metode ini menghaluskan nilai masa lalu dengan bobot eksponensial, memberikan penekanan lebih besar pada data terbaru. Penggunaan data 12 tahun terakhir sebagai data acuan pencatatan masa lalu untuk percobaan peramalan untuk 1 (satu) bulan kedepan. Penggunaan Alpha yang berbeda menguji akurasi dalam situasi aktual. Hasil dari penelitian dengan alpha 0,9 hampir sama dengan nilai aktual dalam meramalkan keadaan satu tahun ke depan dengan error yang paling rendah yaitu MAPE 7,4% dan peramalan persediaan daging ayam broiler sebanyak 13661261,46 ayam.Kata kunci: berbasis web; daging ayam broiler; metode ses.